Themescape quranic visualization / Noorhafidzi Mohd Arif - Noorhafidzi, Mohd Arif (2005)
Themescape Quranic Visualization is a system that helps user to increase the understanding in reading and viewing the content of Al-Quran using the themescape visualization. This is a stand-alone system that requires operating system Widows 98 or above. This report especially focuses on to find ways to improve viewing, accessing or retrieving the content of Al Quran effectively. User can identifY and differentiate the difference between Makkiyah and Madaniyah ayahs in Al-Quran. Besides, user can zoom in and out of ayah Al Quran for better navigation. The problem that emerged among users while reciting Al Quran such as lack of understanding the content and the meaning of Al Quran, and also problem among Quran researchers themselves has made this Themescape Quranic Visualization very useful and easy to learn to overcome all those problems. The system provides lot of information and knowledge for user to know more about Al Quran. It can be accessed anywhere at anytime and suitable for all type of users especially Muslims.